2013
DOI: 10.5964/ejop.v9i4.621
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Disorder: A Review Through the Prism of the Rational-Choice Theory of Neurosis

Abstract: Conversion disorder remains a mystery that has only become more complicated with the decline of the scientific status of psychoanalysis (e.g., Piper, Lillevik, & Kritzer, 2008;Rofé, 2008) and recent neurological findings suggest that this behavior is controlled by biological mechanisms (van Beilen, Vogt, & Leenders, 2010). Moreover, existing theories have difficulty explaining the efficacy of various interventions, such as psychoanalysis, behavior therapy, drug therapy and religious therapy. This article revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 181 publications
0
14
0
Order By: Relevance
“…As noted previously, there is a unanimous agreement among researchers that a diagnostic approach guided by a theory, as suggested by RCTN, which already proved its ability to integrate research and clinical data pertaining to neurosis and psychosis (Rofé, 2000(Rofé, , 2010(Rofé, , 2016Rofé & Rofé, 2013), is preferable over atheoretical, arbitrary diagnostic approaches as proposed by the DSM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted previously, there is a unanimous agreement among researchers that a diagnostic approach guided by a theory, as suggested by RCTN, which already proved its ability to integrate research and clinical data pertaining to neurosis and psychosis (Rofé, 2000(Rofé, , 2010(Rofé, , 2016Rofé & Rofé, 2013), is preferable over atheoretical, arbitrary diagnostic approaches as proposed by the DSM.…”
Section: Discussionmentioning
confidence: 99%
“…Freud assumed the existence of an autonomous, unconscious entity that supposedly had the omnipotent ability to control the patient's daily functions. In contrast, RCTN claims that patients become unaware of their deliberate adaption and maintenance of their mad behaviors, both in neuroses and psychoses, as a result of a complex self-deceptive process (Rofé, 2000(Rofé, , 2010(Rofé, , 2016Rofé & Rofé, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, while biological factors certainly increase the vulnerability to developing fear and phobia, findings have not yet confirmed that these behaviors are controlled by biological mechanisms. A new theory, the Rational-Choice Theory of Neurosis (Rofé, 2010;Y. Rofé & Rofé, 2013), which preserves the psychoanalytic claim that bizarre phobias need to be explained within a theory that accounts for neuroses by one set of theoretical concepts, was used to resolve the theoretical confusion in this field.…”
Section: Introductionmentioning
confidence: 99%